Appropriations locales de la tragédie collective. Approche ethnologique des inondations de novembre 1999 à Cuxac d’Aude - Julien Langumier (Développement Durable et Territoires)
The link between catastrophe and territory can be analysed through inductive or deductive way. The tragic floods which affected Cuxac d’Aude village (Aude, France) in 1999 can be explained by the history of planning suburban neighbourhood in risky places or analysed through the social consequences of the disaster. These approaches answer both to external and synthetic points of view on the event. The ethnographical research proposes another approach which focuses on the bonds with the territory and the practices of the inhabitants and stakeholders. The distinction between account-event, cause-event and memory-event results from the way people take up the catastrophe at a local scale.